Factors Influencing the Accumulation of Recommended Physical Activity among Latinos in the Deep South of the United States (Factores que Influyen en la Acumulación de Actividad Física Recomendada entre Latinos en el Extremo Sur de los Estados Unidos) - Eric P. Plaisance; Larrell L. Wilkinson; Kelsey E. Miller; Luke S. Mahan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Less than 40% of the U.S. population achieves the recommended amount of leisure-time physical activity (LTPA) recommended by the American College of Sports Medicine [ACSM (>150 minutes/week of moderate-intensity or equivalent vigorous-intensity LTPA)]. The number of Hispanic/Latino men and women who report being physically inactive is disproportionately higher than non-Hispanic/Latinos. The purpose of this investigation is to evaluate factors which influence the achievement of meeting ACSM recommendations for LTPA among adults with Hispanic/Latino ethnicity and whites (non-Hispanic/Latino) in the southern United States. Self-reported data collected as part of the Behavioral Risk Factor Surveillance System (BRFSS) was analyzed in male and female Hispanic/Latinos and non-Hispanic/Latino whites using the Andersen Model and Chi Square Analysis to examine the association between variables. Hispanic/Latino men/women were significantly less likely to meet the ACSM recommendations (> 150 minutes/week) compared to non-Hispanic/Latinos. Lower amounts of income, education, and access to health care were all significant factors of whether Hispanic/Latinos in the Deep South achieved the ACSM recommendations for LTPA. Although the percentage of overweight Hispanic/Latinos was considerably higher than White (non-Hispanic/Latino), reported obesity was highest among Whites (non-Hispanic/Latino). LTPA between the two groups differed significantly, suggesting that not achieving the physical activity recommendations is associated with being overweight, but other factors may also contribute to being overweight and obesity. Key words. physical activity, Hispanics, leisure, obesity, overweight, disease.